Mapping the drivers of digital entrepreneurial intention among undergraduate students: A scoping review - Norulhuda, Awang; Mazita, Mokhtar; Noraine, Bahari (Global Academic Excellence (GAE), 2025)
This scoping review aims to map the landscape of research on digital entrepreneurial intention among undergraduate students in higher education institutions. The review specifically focuses on undergraduates in universities and colleges, reflecting the growing interest in fostering entrepreneurship through digital means. Following the PRISMA-ScR (Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews) guidelines, the review analysed studies published between 2020 and 2025. A total of 100 articles were selected using a structured search strategy with keywords related to entrepreneurial intention, higher education institutions, and undergraduate students. The findings reveal several dominant themes across the literature. Key influencing factors on digital entrepreneurial intention include entrepreneurship education, digital literacy, perceived behavioural control, self-efficacy, and institutional support. Many studies adopt theoretical frameworks such as the Theory of Planned Behavior (TPB) and Social Cognitive Career Theory (SCCT) to explain students' intentions to engage in digital entrepreneurship. There is also growing interest in the role of digital tools, online platforms, and experiential learning in shaping entrepreneurial aspirations. The review concludes that while significant progress has been made in understanding digital entrepreneurial intentions, research gaps remain. These include a lack of longitudinal studies, limited focus on socio-cultural contexts, and underrepresentation of data from developing countries.